9+10(6a-1)=

Simple and best practice solution for 9+10(6a-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+10(6a-1)= equation:


Simplifying
9 + 10(6a + -1) = 0

Reorder the terms:
9 + 10(-1 + 6a) = 0
9 + (-1 * 10 + 6a * 10) = 0
9 + (-10 + 60a) = 0

Combine like terms: 9 + -10 = -1
-1 + 60a = 0

Solving
-1 + 60a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 60a = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 60a = 0 + 1
60a = 0 + 1

Combine like terms: 0 + 1 = 1
60a = 1

Divide each side by '60'.
a = 0.01666666667

Simplifying
a = 0.01666666667

See similar equations:

| 3b+2p=29.50 | | x+2x-2x+16=180 | | 35-4x=-10 | | (X-1)(9x^2+3x+1)=0 | | x+2x-x+16=180 | | -3(-7w+3)-6w=5(w-1)-8 | | 5N+34=2(1-9N) | | 10-5(6)=20 | | 5.1a+10=71.2 | | 0.25(4x-2)=x-.50 | | 8(x+4)=4(x+8)+4x | | 9x^4+27x^3-13x^2-12x+4=0 | | 10x+2y=54 | | cospix=.5 | | 7(9x-1)=2(9x+1)+846 | | -14+126x=14+84x | | 13x+89=180 | | 2x-(x+7)+9= | | 12n(n+3)+15=396 | | 22=3y+x | | 7(18x-2)=14(6x+1) | | 5(2x+3)(4x-1)=0 | | 7x+15=6x+20 | | 0.25(4x-2)=x-.25 | | 4x+8y-2(7x-4y)= | | 63+8(6x-1)=7(6x+1) | | -8(b-862)=-560 | | 16=8c | | 2.50(m+15.00)=662.5 | | 2.5r=95 | | 6(3x-6)=10x | | a+3ab+6+7a-2ab-1=0 |

Equations solver categories